(untitled) (Global Journal of Human-Social Science, 2017)
In modern African politics, terrorism and failed state syndrome have became prevalent and a challenge to democratic values and virtues of good governance, posing great threat and stress to the survival of domestic political systems. This increasing political stress is a product of competition and struggle for power and supremacy among players in the executive and legislative organs of government, which has reduced the parliament to a rubber stamp of power seekers as well as the use of electoral violence as instruments of regime change. Therefore, this study seeks to examine the root cause of political struggle and problems of good governance in Africa by analyzing the variables of intra-elite crisis in the parliament and the quest for establishment of spheres of influence by players in the executive arm.